Cultivating Multicultural Values in Learning History: A Unifier of the Nation’s Plurality - Slamet, Slamet (Universitas Negeri Semarang, 2017)
Indonesia is full of diversity, either ethnic, religious, culture, custom, racial, territorial, and so on. In having a common perception onIndonesian diversityas a nation, multicultural education has become a necessity. Incorporating multicultural education into the curriculum is very urgent, at least by incorporating it with other relevant subjects, such as Civics, History, and Religion. Multicultural education is a response to the growing diversity of school populations, as well as the demands of equal rights for every citizen. Another dimension, multicultural education is the development of curricula and educational activities to tap into the views, history, achievements and concerns of non-Europeans. Multicultural education encompasses all learners regardless of group, such as: gender, ethnic, racial, cultural, social, territorial, and religious strata, which has become a demand and necessity in building a new Indonesia. However, multicultural education requires an in-depth study of the concepts and praxis of its implementation, even to the present the concept of multicultural education has not been studied seriously in education. However, when judicially judged, Act Act no. 20/2003 on the National Education System has provided an opportunity to elaborate further on the concept of multicultural education, particularly in Article 4 paragraph (1) which regulates the implementation of education which takes into consideration the diverse cultural values ​​of society.